Answer:
Yes, the two equations are equivalent.
Explanation:
For the first equation, we will solve for x.
2x + 4 = 10
Subtract 4 from both sides...
2x + 4 = 10
-4 -4
It then becomes
2x = 6
Then we divide by 2 on both sides.
2x = 6
2 2
Then the answer is...
x = 3
Now let's also solve for x on the second equation.
3x + 6 = 15
Subtract 6 on both sides to get x alone...
3x + 6 = 15
-6 -6
Then it is..
3x = 9
Lastly, divide by 3 on both sides...
3x = 9
3 3
Then it becomes
x = 3.
Then we see that both equations have x = 3, meaning when both x's = 3, then both equations will be equivalent. I hope this helps, and I hope it is not wrong, but I don't think it is.